A case complicated by floating fractured stent 141 months after nitinol stent implantation in the superficial femoral artery. Issue 2 (August 2017) - Tsujimura, Takuya; Ishihara, Takayuki; Iida, Osamu; Fujita, Masashi; Okamoto, Shin; Uematsu, Masaaki
Abstract: An 80-year-old man received the implantation of a self-expanding stent (Luminexx, Bard, Inc., Murray Hill, NJ, USA) for an in-stent restenosis (ISR) lesion in the superficial femoral artery. However, angiography 141 months after the Luminexx stent implantation showed 90% ISR and a floating fractured stent in the Luminexx site. Furthermore, the floating fractured stent strut itself was completely separated and flowed toward the posterior tibial artery. The stent strut was removed by a catheter for removing intravascular foreign substances. <Learning objective: We report a case of a floating fractured stent 141 months after stent implantation in the superficial femoral artery (SFA). Although this case is rare, in endovascular therapy with stenting for SFA, it is necessary to consider the risk of stent fracture in the very late phase.>